2009
DOI: 10.1364/oe.17.006293
|View full text |Cite
|
Sign up to set email alerts
|

All-optical memory based on the injection locking bistability of a two-color laser diode

Abstract: We study the injection locking bistability of a specially engineered two-color semiconductor FabryPérot laser. Oscillation in the uninjected primary mode leads to a bistability of single mode and two-color equilibria. With pulsed modulation of the injected power we demonstrate an all-optical memory element based on this bistability, where the uninjected primary mode is switched with 35 dB intensity contrast. Using experimental and theoretical analysis, we describe the associated bifurcation structure, which is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 25 publications
5
48
0
Order By: Relevance
“…Apart from their scientific appeal, these nonlinear dynamics can also be exploited and used for technological applications. For example, optically injected lasers have been implemented as an all-optical memory or switch, allowing for a toggling between two different stable states by external trigger signals [OSB09a,OSB12]. Furthermore, optically injected Parts of this section have been published in [LIN12b,LIN13].…”
Section: Quantum-dot Laser Dynamicsmentioning
confidence: 99%
“…Apart from their scientific appeal, these nonlinear dynamics can also be exploited and used for technological applications. For example, optically injected lasers have been implemented as an all-optical memory or switch, allowing for a toggling between two different stable states by external trigger signals [OSB09a,OSB12]. Furthermore, optically injected Parts of this section have been published in [LIN12b,LIN13].…”
Section: Quantum-dot Laser Dynamicsmentioning
confidence: 99%
“…1 Recently, dual-mode lasers, a family that includes vertical cavity surface emitting lasers (VCSELs), ring lasers, photonic crystal lasers, and two color Fabry-Pérot (FP) lasers, subjected to a single optical injection have been studied due to potential applications in all-optical signal processing. [2][3][4][5][6] An additional injected mode can also add functionality to multimode FP lasers. [7][8][9] However, the understanding of these dual injected FP lasers is complicated by the effects of the uninjected modes.…”
mentioning
confidence: 99%
“…We have previously shown that a four dimensional rate equation model accurately describes the dynamics of a two color laser subject to optical injection into one of the two modes. 6 In the dual injection case, this model generalizes to a five-dimensional system for the normalized complex fields, E 1/2 , and the normalized excess carrier density, n, whose dynamic evolution is given by…”
mentioning
confidence: 99%
See 2 more Smart Citations